Introduction: Towards a Multifaceted History of Early Modern Women in the Low Countries - Lamal, Nina; van Deinsen, Lieke; Dietz, Feike (Early Modern Low Countries, 2025)
Introduction to the special issue 'Towards a Multifaceted History of Early Modern Women in the Low Countries'